Impact of Hemodialysis on Serum Zinc and Copper Level in CKD Patients - Shehab Elzain Hamad Balla, Amar Mohamed Ismail (Journal of Applied Pharmaceutical Science, 2016)
The aim of this study was to assess the effect of HD on zinc and copper level among CKD patients. A cross-sectional study included 40 subjects (15 female and 25 male) from academic hospital aged (22-80 years old) were included, timed pre and post-hemodialysis samples were collected. Serum zinc, copper, urea and creatinine were measured by using atomic absorption spectroscopy 210-VGP® and Mindray Bs-200 respectively, and BMI was estimated. Paired t-test analyses showed significant decrease in mean copper, urea and creatinine with p-value (0.025, 0.000 and 0.000) respectively, while significant increase was observed in zinc level p-value 0.035. Person's correlation showed positive correlation between change in zinc level and reduction in urea, and no correlation noted between change in serum copper level and reduction in urea and creatinine. In conclusion HD decrease copper and increase zinc as both are antagonists, might play a vital role in pathogenesis of related disorders in CKD Patients.
Keywords: Zinc, copper, CKD, dialysis and hemodialysis.